Determining Factors and IT Adoption by Auditing Limited Liability Partnerships: Mediating Effect of IT Confidence - Thottoli, Mohammed Muneerali; Ahmed, Essia Ries (International Journal of Economics, Management and Accounting, 2023)
This research study examines the effect of information technology (IT) determining factors (IT awareness and IT proficiency) and IT adoption by auditing Limited Liability Partnerships (LLPs). This study also examines the mediating effect of IT confidence on the link between the determining factors and IT adoption by auditing LLPs. Data were gathered from 143 partners who are practicing chartered accountants registered as LLPs located in Kerala, India. The conceptual model is tested using structural equation modeling based on partial least squares. The findings confirm the direct effect of IT awareness, IT confidence on IT adoption as well as the mediating effects of IT confidence on the relationship between IT proficiency and IT adoption by auditing LLPs. The research study is performed only in the Indian LLPs perspective and future studies can be performed in other nations as well to generalize the findings. The findings of this research study can be used to guide practicing chartered accountants registered as LLPs, governing bodies of practicing auditors, and software developers while expanding the IT adoption by auditing LLPs. The determining factors of IT adoption have great potential for auditors of practicing firms for transforming from manual audits by adopting IT-enabled auditing tools to facilitate their audit services. The present research study gives valuable insight into the critical mediating role of IT proficiency and other IT variables as activating factors that impact auditing practice efficiency of auditing LLPs.